Information for contributors and readers for issue 1-2019 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Technical Courier for the year 2018.Serbian Citation Index has indexed the Military Technical Courier articles from 1990 to 1999